2020
DOI: 10.1177/1055665620935363
|View full text |Cite
|
Sign up to set email alerts
|

Embryologically Based Classification Specifies Gender Differences in the Prevalence of Orofacial Cleft Subphenotypes

Abstract: Background: A recently published validated classification system divides all orofacial cleft (OFC) subphenotypes into groups based on underlying developmental mechanisms, that is, fusion and differentiation, and their timing, that is, early and late periods, in embryogenesis of the primary and secondary palates. Aims: The aim of our study was to define gender differences in prevalence for all subphenotypes in newborns with OFC in the Netherlands. Methods: This was a retrospective cross-sectional study on child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 32 publications
3
11
1
Order By: Relevance
“…The current study revealed that most of the participants were male participants. This finding is consistent with previous findings, 21 22 23 24 25 of which the male predominance in these types of birth defects was mainly reported. In a literature review by Mairaj et al, it was revealed that male predominance was reported for the prevalence of cleft lip and palate with a male/female sex ratio of 1.81 (CI 95%: 1.75–1.86).…”
Section: Discussionsupporting
confidence: 94%
“…The current study revealed that most of the participants were male participants. This finding is consistent with previous findings, 21 22 23 24 25 of which the male predominance in these types of birth defects was mainly reported. In a literature review by Mairaj et al, it was revealed that male predominance was reported for the prevalence of cleft lip and palate with a male/female sex ratio of 1.81 (CI 95%: 1.75–1.86).…”
Section: Discussionsupporting
confidence: 94%
“…A study conducted in the Netherlands determined that CL/P was more common in males while cleft palate (CP) was more common in females (Pool et al, 2020). While one study concluded similar results (Bui et al, 2018a), other studies identified CL/P, CL, and/or CP to be more prevalent in females (Omo-Aghoja et al, 2010;Kalaskar et al, 2013;Mbuyi-Musanzayi et al, 2018;Ali & Hamid, 2019) and CLP, CL and alveolus, and CP to be prevalent in males (Mbuyi-Musanzayi et al, 2018;Ali & Hamid, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the impact of genetic variants on OFC risk for males and females differs (Carlson et al, 2018). Furthermore, Pool et al (2020) have recently found highly significant gender differences in the prevalence of OFC subphenotypes in the Netherlands. These data underline the fact that males and females must be assessed separately.…”
Section: Gender Differencesmentioning
confidence: 99%
“…Additionally, the affected anatomical structures (lip, premaxilla/maxilla, hard palate, soft palate, and/or uvula), laterality, and the morphological feature of each anatomical structure (complete, incomplete, submucous, or hypoplasia) were noted, and any other head-neck anomalies with respect to soft tissues, tongue, nasal septum, ears, eyes, eyelids, and individual bones of the neurocranium and facial skeleton (Luijsterburg et al, 2014). This data set was previously used by Pool et al (2020). For data collection, the principles outlined in the Declaration of Helsinki were followed.…”
Section: Data Collection: Inclusion and Exclusion Criteriamentioning
confidence: 99%
See 1 more Smart Citation